Kebermaknaan Hidup ODHA ditinjau dari Ikhlas dan Dukungan Sosial - Ramiza, Kiki (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2017)
The purpose of this study is to determine the correlation between ikhlas and social support to the meaningfulness of life in people living with HIV. Subjects in this study amounted to 75 people living with HIV (People With HIV / AIDS). Data analysis used is multiple regression test and different test. Meaningfulness of life measured using the scale used by Febriyanti (2011) is based on the theory put forward by Bastaman (2007), ikhlas is measured using a scale from Chizanah and Hadjam (2013), and social support using a multidimensional scale of perceived social support from Zimet, Dahlem, Zimet, and Farley, 1988 adapted by researchers. The results of this study indicate that there is a significant relationship between ikhlas and social support to the meaningfulness of life in people living with HIV.